A SIMPLE TUBE CONTROLLER FOR EFFICIENT ROBUST MODEL PREDICTIVE CONTROL OF CONSTRAINED LINEAR DISCRETE TIME SYSTEMS SUBJECT TO BOUNDED DISTURBANCES - Raković, S.V.; Mayne, D.Q. (IFAC Proceedings Volumes, 2005)
We present a simple tube controller for efficient robust model predictive control of constrained linear, discrete-time systems in the presence of bounded disturbances. The proposed control policy ensures that controlled trajectories are confined to a given tube despite uncertainty. The robust optimal control problem that is solved on-line is a standard quadratic programming problem of marginally increased complexity compared with that required for model predictive control in the deterministic case. We show how to optimize the tube cross section, how to construct an adequate tube terminal set and we establish robust exponential stability of a suitable robust control invariant set (the ‘origin’ for uncertain system) with enlarged domain of attraction.